Methodology Of Managerial Innovations In Governmental Management - Serhiy M. Shkarlet, Vadym A. Tkachuk, Nadiia P. Reznik, Yuliia S. Naumko, Valeriia Yu. Prokopenko (International Journal of Advanced Science and Technology, 2020)
Conceptual and methodological approaches to the process of forming managerial innovation-acmeological strategies in the public administration system are generalized. Methodological approaches to the investigation of innovations in governmental management were analyzed. The necessity to study innovative changes is substantiated in the functions and strategic orientations of the state administration of Ukraine. Meta-paradigmal and interdisciplinary character of such methodology that combines several approaches and uses methodological fundamentals of innovative management were also substantiated.